The Global Financial Crisis and Adjustment to Shocks in Kenya, Tanzania, and Uganda : A Balance Sheet Analysis Perspective - Masha, Iyabo (Departmental Papers; Departmental Paper ;, 2009)
This paper analyzes the impact of the global financial crisis on the banking systems in Kenya, Tanzania, and Uganda, and their responses to it, using information from banking system balance sheets. The paper undertakes two distinct analyses. In the first analysis, the focus is on the trend in intersectoral balances and positions in the long run, using annual data for 2001-08. The second analysis uses monthly data for December 2007-May 2009 to determine how intersectoral balance sheets adjusted in the short run to sudden changes in the economic environment during the recent global financial crisis.